SDG13 - climate action : combating climate change and its impacts - Doni, Federica; Gasperini, Andrea; Torres Soares, João (Concise guides to the United Nations Sustainable Development Goals., 2020)
SDG13 - Climate Action: Combatting Climate Change and its Impactswill consider empirical and science-based analysis to explore a wide range of practical implementation tools and mechanisms, enabling conditions, and monitoring and reporting tools, to demonstrate the potential innovation in implementing SDG13.